Standup time estimation of undercut moist sand slope using numerical simulation - Laddawon Dul (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Pitwalls stability would be jeopardized when they were undercut. The undercutting, excavating at the toe of the pitwall or slope, could cause a slope failure. After undercut, the loads or stresses the slope have been changed, both magnitudes and directions, in the slope and formed an arch action. The undercut slope displaces slowly over a period of time until it fails. This is influence of time on material deformation which was creep behavior of material. A series of numerical simulations, using 3DEC, was performed as preliminary study of standup time of undercut slopes. The simulation was used Burgers viscoplastic model and was controlled by creep parameters and basic engineering properties. The models were used silica sand No.6 with controlling moisture 10% which was good adhesion of sand. The moist sand was represented for determining parameters from laboratory which were assigned to numerical simulation. Basic physical properties were obtained from Uniaxial Compressive Strength and direct shear tests. The parameters of creep were calculated by a series of uniaxial compression creep tests which were used Burgers model to fit the lab results. The creep test was investigated 2 term as long term and short term of creep behavior. The numerical models were made of moist sand and placed on a low friction angle bed at 18.5ᵒ. The slope inclinations varied from 15 to 50 degrees which were 2 more than and 2 less than of interface friction angle bed. From the numerical simulation results, the standup time of the undercut slope, steeper than the friction angle bed, was approximately 10 and 50 minutes at 0.3 m maximum undercut width. The standup time extended drastically to 251 and 371 minutes when the slope inclinations were 18 degrees and 15 degrees at 0.8 m maximum undercut width, respectively. As same increase in density of moist sand, standup time of inclination angle slope 50 and 30 were 25 and 130 min at maximum undercut width 0.3 m. When decreasing inclination angle slope to 18 and 15, the standup time were 435-1,510 min at maximum undercut width 0.8 m. Relationships between slope inclination, undercut width and standup time were drawn. When the slope inclination was shallower than the friction angle of the bed, its standup time and undercut width were longer and wider than the steeper slope inclination. Conclusively, the standup time was inversely proportional to the undercut width and the inclination angle. The shallower inclination angle slope extended the standup time of undercut slope and the maximum undercut width. In addition, the standup time of undercut slope was required the effect of arch action. The stresses at the center of undercut slope transferred to the sides of slope in formed arch shape. The tangential stresses at both sides were soared until beyond to support at tertiary of creep behavior. The undercut slope stability was failed at this time.